Multiparametric magnetic resonance imaging facilitates reclassification during active surveillance for prostate cancer. (10th December 2020) - Fujihara, Atsuko; Iwata, Tsuyoshi; Shakir, Aliasger; Tafuri, Alessandro; Cacciamani, Giovanni E.; Gill, Karanvir; Ashrafi, Akbar; Ukimura, Osamu; Desai, Mihir; Duddalwar, Vinay; Stern, Mariana S.; Aron, Manju; et al.
Abstract : Objective: To investigate the utility of multiparametric magnetic resonance imaging (mpMRI) in the reassessment and monitoring of patients on active surveillance (AS) for Grade Group (GG) 1 prostate cancer (PCa). Patients and Methods: We identified, from our prospectively maintained institutional review board‐approved database, 181 consecutive men enrolled on AS for GG 1 PCa who underwent at least one surveillance mpMRI followed by MRI/prostate biopsy (PBx). A subset analysis was performed among 68 patients who underwent serial (at least two) mpMRI/PBx during AS. Pathological progression (PP) was defined as upgrade to GG ≥2 on follow up biopsy. Results: Baseline MRI was performed in 34 patients (19%). At a median follow‐up of 2.2 years for the overall cohort, the PP was 12% (6/49) for Prostate Imaging Reporting and Data System (PI‐RADS) 1–2 lesions and 37% (48/129) for the PI‐RADS ≥3 lesions. The 2‐year PP‐free survival rate was 84%. Surveillance prostate‐specific antigen density ( P < 0.001) and surveillance PI‐RADS ≥3 ( P = 0.002) were independent predictors of PP on reassessment MRI/PBx. In the serial MRI cohort, the 2‐year PP‐free survival was 95% for the No‐MRI‐progression group vs 85% for the MRI‐progression group ( P = 0.02). MRI progression was significantly higher in the PP (62%) than in the No‐PP (31%) group ( P = 0.04). If serial MRI were used for PCa surveillance and biopsy were triggered based only on MRI progression, 63% of PBx might be postponed at the cost of missing 12% of GG ≥2 PCa in those with stable MRI. Conversely, this strategy would miss 38% of those with upgrading to GG ≥2 PCa on biopsy. Stable serial mpMRI correlates with no reclassification to GG ≥3 PCa during AS. Conclusion: On surveillance mpMRI, PI‐RADS ≥3 was associated with increased risk of PCa reclassification. Surveillance biopsy based only on MRI progression may avoid a large number of biopsies at the cost of missing many PCa reclassifications.